A Tourist guide to notable Philippine historical landmarks, monuments and shrines - Layug, Benjamin Locsin (Quezon City, Philippines : New Day Publishers, 2010)
Many of the shrines, monuments and landmarks mentioned in this book are under the administration of the National Historical Institute, locally called Pambansang Suriang Pangkasaysayan the government agency primarily tasked with the preservation of Philippine history and cultural heritage.
1. Ilocos Region -- 2. Central Luzon region -- 3. National Capital region -- 4. Southern Tagalog Region -- 5. Bicol Region -- 6. Western Visayas region -- 7. Central Visayas Region -- 8. Eastern Visayas Region -- 10. Western Mindanao Region.
Includes bibliographical references.
Keywords: HISTORIC SITES -- PHILIPPINES